THE EFFECT OF WORK ENVIRONMENT AND SELF EFFICACY ON THE QUARTER LIFE CRICIS PHENOMENON AMONG GROUP M INDONESIA EMPLOYEES - Achvita Dien Adira; Muhamad Azis Firdaus; Widhi Ario Bimo (Manager : Jurnal Ilmu Manajemen, 2025)
This study aims to analyze the effect of work environment and self-efficacy on the phenomenon of quarter life crisis in employees of advertising company Group M Indonesia. This study uses a quantitative approach with path analysis techniques to test the relationship between variables. Data were collected through distributing questionnaires to Group M Indonesia employees and analyzed using statistical software, namely SmartPLS 4. The results showed that the work environment partially had no significant effect on quarter life crisis (path coefficient = -0.175; P-value = 0.604; T-statistic = 0.519). Self efficacy also has no significant effect on quarter life crisis (path coefficient = -0.070; P-value = 0.805; T-statistic = 0.247). However, the work environment was shown to have a significant influence on self-efficacy (path coefficient = 0.653; P-value = 0.000; T-statistic = 5.112). Simultaneously, work environment and self efficacy did not show significant influence on quarter life crisis. The conclusion of this study is that work environment factors and self efficacy partially or simultaneously have no significant effect on quarter life crisis, except for the effect of work environment on self efficacy which is proven significant.